(untitled) (Jurnal EurekaMatika, 2023)
ABSTRACT The growth in the number of online shop members has caused the value of e-commerce transactions in Indonesia to increase. This resulted in increased distribution of goods at PT. Indah Logistik Cargo. One of the constraints at PT. Indah Logistik Cargo is inefficient routes the distribution of packages. Distribution problem at this delivery service company include the Traveling Salesman Problem (TSP), which can be solved using the Cheapest Insertion Heuristic (CIH) algorithm. In this paper, the solution is carried out manually and also utilizes the Python programming language to optimize the delivery service travel path. Factual data owned by PT. Indah Logistik Cargo states that the total distance for delivering goods is 51.600 meters. Meanwhile, based on the results of manual calculations using the CIH algorithm, a total distance of 51.550 meters was obtained, which is smaller by a difference of 50 meters from the factual data. Furthermore, the results of calculations using the Python programming obtained 47.150 meters, or a difference of 4.450 meters. Therefore, the use of the CIH algorithm is proven to provide a path with a smaller total distance traveled. ABSTRAK Peningkatan jumlah anggota online shop membuat nilai transaksi e-commerce di Indonesia mengalami kenaikan. Hal ini mengakibatkan meningkatnya pendistribusian barang pada PT. Indah Logistik Cargo. Kendala pada PT. Indah Logistik Cargo adalah keterlambatan penyaluran paket ke para konsumen akibat jalur lintasan yang tidak efisien. Permasalahan pendistribusian pada perusahaan jasa pengiriman ini termasuk permasalahan Travelling Salesman Problem (TSP) yang dapat diselesaikan menggunakan Algoritma Cheapest Insertion Heuristic (CIH). Pada tulisan ini, penyelesaian masalah tersebut dilakukan secara manual dan juga menggunakan bahasa pemrograman Python. Data faktual yang dimiliki PT. Indah Logistik Cargo bahwa total jarak pengiriman barang yaitu 51.600 meter. Sementara, berdasarkan hasil perhitungan dengan algoritma CIH secara manual diperoleh total jarak 51.550 meter, yang lebih kecil dengan selisih 50 meter dari data faktual. Sedangkan, hasil perhitungan dengan bahasa pemrograman Python diperoleh 47.150 meter, atau mempunyai selisih 4.450 meter. Oleh karena itu, penggunaan algoritma CIH terbukti memberikan lintasan dengan total jarak tempuh yang lebih kecil.